Record of Discussions Fiftieth Meeting National Development Council - Planning Commission (Planning Commission, 2002)
The National Development Council (NDC) held its Fiftieth Meeting at Vigyan Bhavan, New Delhi on the 21st December, 2002 under the Chairmanship of Shri Atal Bihari Vajpayee, Prime Minister and Chairman of the Council, to consider and adopt the draft of the Tenth Five Year Plan Document, covering the period 2002-2007.
Government of India Planning Commission
Government of India Planning Commission